2009
DOI: 10.1111/j.1537-2995.2009.02203.x
|View full text |Cite
|
Sign up to set email alerts
|

First transmission of human immunodeficiency virus Type 1 by a cellular blood product after mandatory nucleic acid screening in Germany

Abstract: This case represents the first documented HIV-1 transmission by transfusion of red blood cells after mandatory introduction of HIV-1 NAT for blood screening in Germany. Low viral load and mismatches in the primer/probe region might explain the detection failure of the NAT screening assay. A certain risk remains that new virus variants contain mutations at positions critical for amplification or detection of viral genomes. An option to reduce the risk of a detection failure by NAT is the simultaneous use of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 22 publications
0
87
0
7
Order By: Relevance
“…Rhesus is a seropositive monkey). (Schmidt et al 2009). In Singapore, it has been reported that a blood transfusion was the source of an HIV infection.…”
Section: Infectious Blood and Blood Products From Donors At The Seronmentioning
confidence: 99%
“…Rhesus is a seropositive monkey). (Schmidt et al 2009). In Singapore, it has been reported that a blood transfusion was the source of an HIV infection.…”
Section: Infectious Blood and Blood Products From Donors At The Seronmentioning
confidence: 99%
“…The cases were traceable to false-negative test results in the routine NAT assays due to new variants of the common HIV-1 subtype B missed by the assays' design. Recently, details of these 2 transmission cases and a number of related cases of false-negative HIV-1 NAT screening results have been published [8,9,10,11,12]. In addition, we must emphasize that cases of false-negative HIV-1 NAT based on low viral load combined with suboptimal NAT sensitivity in the screening of mini pools cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…В 2009 году M. Schmidt и соавт. [43] опубликован случай передачи HIV при переливании реципиенту отмытых эритроцитов при отрицатель-ном результате NAT-тестирования донорской кро-ви. При проведении эпидемиологического рассле-дования было установлено, что чувствительность детекции HIV RNA автоматической ПЦР-станции в мини-пулах оказалась недостаточной для выявле-ния вирусной РНК.…”
Section: диагностика Hiv-инфекции у потенциальных доноров органов и тunclassified